Analisis Kecelakaan Kerja dan Perawatan Kendaraan untuk Meningkatkan Produktivitas Karyawan PT. XYZ - Abdullah Ali Aufa; Dafa Achmad Keysa; Muhammad Rizki Aflahul Muzhidin (Jurnal Riset Teknik Industri, 2026)
Abstract. Operational activities in logistics service companies have a high risk of workplace accidents, particularly due to human factors and vehicle conditions. These issues are often caused by suboptimal vehicle maintenance systems and low implementation of occupational safety practices. This study aims to analyze the factors causing workplace accidents and evaluate vehicle maintenance systems through the application of Kaizen and Failure Mode and Effect Analysis (FMEA) methods at PT. XYZ. Data were obtained from workplace accident reports, vehicle maintenance records, vehicle service activities, and vehicle downtime (aging service) data. Descriptive statistical analysis was employed to identify patterns of workplace accidents, vehicle maintenance activities, and vehicle downtime. The Kaizen method was used to identify root causes of problems, while FMEA was applied to assess potential vehicle failures through the calculation of Risk Priority Numbers (RPN). The results indicate that workplace accidents are generally caused by delays in periodic maintenance, inadequate preventive inspections, and low driver awareness of safety practices. The application of Kaizen and FMEA helps determine improvement priorities and enhance the effectiveness of vehicle maintenance in supporting workplace safety and operational productivity within the company. Abstrak. Aktivitas operasional pada perusahaan jasa logistik memiliki risiko kecelakaan kerja yang tinggi, terutama akibat faktor manusia dan kondisi kendaraan. Masalah ini banyak dipicu oleh sistem perawatan kendaraan yang belum optimal serta rendahnya penerapan keselamatan kerja. Penelitian ini bertujuan menganalisis faktor penyebab kecelakaan kerja dan mengevaluasi sistem perawatan kendaraan melalui penerapan metode Kaizen dan Failure Mode and Effect Analysis (FMEA) pada PT. XYZ. Data diperoleh dari laporan kecelakaan kerja, riwayat perawatan kendaraan, aktivitas service kendaraan, serta data downtime (aging service) armada operasional. Analisis dilakukan menggunakan statistik deskriptif untuk melihat pola kecelakaan kerja, aktivitas perawatan kendaraan dan downtime kendaraan. Kaizen digunakan untuk mengidentifikasi akar penyebab masalah, sedangkan FMEA menilai potensi kegagalan kendaraan melalui perhitungan Risk Priority Number (RPN). Hasil penelitian menunjukkan bahwa kecelakaan kerja umumnya disebabkan oleh keterlambatan perawatan berkala, minimnya inspeksi preventif, dan rendahnya kesadaran pengemudi. Penerapan Kaizen dan FMEA membantu menentukan prioritas perbaikan serta meningkatkan efektivitas perawatan kendaraan untuk mendukung keselamatan kerja dan produktivitas operasional perusahaan.